The Immunoregulatory Activities of Activated Protein C in Inflammatory Disease - McDonnell, Cormac J.; Soule, Erin E.; Walsh, Patrick T.; O'Donnell, James S.; Preston, Roger J. S. (Seminars in Thrombosis and Hemostasis, 2018)
Tissue injury prompts the initiation of host defense responses to limit blood loss, restrict pathogen entry, and promote repair. Biochemical and cellular pathways that lead to blood coagulation serve a fundamental role in generating a physical barrier at the wound site, but have also evolved to promote immune response to injury. Similarly, anticoagulant pathways that attenuate clot formation also regulate innate and adaptive immune responses. Of particular importance is activated protein C (APC) which serves as a principal regulator of thrombin generation, shapes the innate immune response to infection, and has been shown to contribute to the adaptive immune response in several preclinical models of autoimmune disease. APC controls blood coagulation by proteolytic degradation of procoagulant activated cofactors essential for fibrin clot development, but also cleaves multiple additional substrates and interacts with cell surface receptors to exert additional physiologically important roles. In this review, we focus on the molecular mechanisms utilized by APC to limit inflammation and, in particular, current understanding of the basis for APC anticoagulant and signaling activities. In particular, we provide an overview of established and emerging signaling pathways initiated by APC on endothelial cells, monocytes, neutrophils, dendritic cells, and T cells to control and regulate immune cell physiology. Finally, we consider the impact of APC activity in the context of both acute and chronic inflammatory disease, and the continuing efforts to harness the immunoregulatory properties of recombinant APC for therapeutic use.
Keywords: activated protein C; monocytes; neutrophils; cell signaling; T cells